Fostering of innovation within green growth industries: How the Danish national innovation systems affect supply-network enabled innovation. Issue 4 (6th November 2017) - Kavin, Lone; Stentoft, Jan
Abstract : Purpose: This paper aims to analyse how the political, relational and institutional contexts of the offshore wind industry affect supply-network-enabled innovation (SNEI) and to identify significant possibilities for obtaining the overall target of reducing the cost of producing energy based on the offshore wind industry. Design/methodology/approach: Through an embedded single-case study, the contextual conditions of SNEI within the relatively immature offshore wind energy industry are investigated. Findings: The national system of innovation only affects product innovation within the industry. Process innovation, which is needed to make the industry grow and mature, seems lesser supported. Different levels of maturity exist among the actors within the industry, which creates barriers for SNEI. To help the offshore wind industry grow, the educational and research system can promote integration of companies by helping the actors to design best practices and manage their business processes according to some generic goals and practices. Additionally, the political system must provide clearer intentions for a sustainable future. Practical implications: This paper provides insights into how SNEI can be applied within the Danish offshore wind industry to foster competitive advantages against energy recovered based on fossil fuels. Originality/value: The paper contributes to the rather immature field of research on SNEI with empirical data from a network of companies. Furthermore, it adds to the emerging research area of political-initiated development of renewable energy sources.